Efficacy of misoprostol over dinoprostone gel as a cervical ripening agent: a comparative study - Nimbalkar, Pankajkumar B.; Patel, Jaldhara N.; Thakor, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Timely induction of labour could reduce maternal mortality and morbidity as well as assure a delivery of healthy baby. The objective of this study was to evaluate the efficacy of Misoprostol as a cervical ripening agent and its comparison with Dinoprostone gel in terms of success rate, safety, side effects and patient compliance. Methods: A total of 250 pregnant women requiring induction of labor were recruited. Out of 250 cases, 150 were induced with 50 microgram Misoprostol and 100 cases with 0.5 mg intracervical Dinoprostone gel during September 2014 to August 2017 at the department of Obstetrics and Gynaecology, GMERS Medical College, Dharpur-Patan. Written and informed consent was taken from the patients. Outcome measures, such as change in Bishop's score, need of augmentation, induction delivery interval; complications like hyperstimulation, fever and meconium passage were compared between two groups. Statistical analysis was performed by Epi Info 7. Results: Age range of the patients was 21 to 35 years. 74.8% of the patients were in 21-25 years age groups. 50.4% patients were multigravida. 57.6% patients had more than 37 weeks of pregnancy. 50.4% of the patients had premature rupture of membrane as indication of labour. The mean Bishop's score for induction was 3.21 in Misoprostol group. 81.3% patients in Misoprostol group and 93% of patients in Dinoprostone group were delivered by vaginal delivery. 60% patients delivered within 6 hours in Misoprostol group. (Misoprostol: 60%, Dinoprostone: 27%, p<0.001). Incidence of thin meconium was 11.3% in Misoprostol group, 9% in Dinoprostone group. In Misoprostol group 3.3 women had fever after induction. Conclusions: Vaginal misoprostol is more efficacious in cervical ripening and for induction of labor than Dinoprostone.